Identification of an enhancer and an alternative promoter in the first intron of the α-fetoprotein gene - Scohy, Sophie (Oxford University Press, 2000)
In this study we have characterized a positive regulatory region located in the first intron of the α-fetoprotein (AFP) gene. We show that the enhancer activity of the region depends on a 44 bp sequence centered on a CACCC motif. The sequence is the target of the two zinc fingers transcription factors BKLF and YY1. The introduction of a mutation destroying the CACCC box impairs the binding of BKLF but improves that of YY1. Moreover, the mutated sequence behaves as a negative control element, suggesting that BKLF behaves as a positive factor and that YY1 is a negative one. We also demonstrate the existence of a novel, tissue-specific AFP mRNA isoform present in the yolk sac and fetal liver which initiates from an alternative promoter located ∼100 bp downstream of the enhancer element. The transcriptional start site controlled by this new promoter (called P2), was mapped to 66 bp downstream of a TATA box. A putative AUG translation site in-frame with exon 2 of the classical gene was found 295 bp downstream of the transcription start site. Like the traditional AFP promoter (P1), the P2 promoter is active in the yolk sac and fetal liver. Embryonic stem cells with an AFP knock-in gene containing either the P2 promoter or deleted for it were isolated and comparative analysis of embryonic bodies derived from these cells suggests that the P2 promoter contributes to early expression of the AFP gene.